2014
DOI: 10.1111/ctr.12464
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive therapies after intestinal transplant modulate the expression of Th1 signature genes during acute cellular rejection. Implications in the search for rejection biomarkers

Abstract: Gene expression of Th1 response mediators is higher during ACR. Triple IS group showed significantly lower expression of pro-inflammatory Th1 mediators during mild ACR indicating that use of these markers to monitor rejection can be affected by the IS treatment used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…However, in the later period of the acute allograft rejection progress, the increased IP-10 levels combined with the decreased TARC expression revealed that the T H 1 chemokines obtain an advantage due to the antagonistic relationship between the chemokines secreted by T H 1 and T H 2 cells. This inference is consistent with the results in a previous report that IP-10 gradually became the protagonist during the acute allograft rejection progress [32]. …”
Section: Discussionsupporting
confidence: 94%
“…However, in the later period of the acute allograft rejection progress, the increased IP-10 levels combined with the decreased TARC expression revealed that the T H 1 chemokines obtain an advantage due to the antagonistic relationship between the chemokines secreted by T H 1 and T H 2 cells. This inference is consistent with the results in a previous report that IP-10 gradually became the protagonist during the acute allograft rejection progress [32]. …”
Section: Discussionsupporting
confidence: 94%
“…A reason for the paucity of clinical studies may be the perceived confounding effect of immunosuppression (tolerance induction regimens, maintenance immunosuppression) and its impact on the kinetics of various biomolecules [86,87], adding to all the other causes of heterogeneity encountered in a clinical setting. Indeed, a clinical study found that, whereas the expression of intragraft IFN-gamma, CXCL10, and CXCL11 was clearly increased during rejection, rejecting individuals receiving reduced immunosuppression showed a 13-fold increase in IFN-gamma expression and a 9-fold increase in CXCL10 expression, while patients with more intense immunosuppression revealed a significantly lower increase [88].…”
Section: Markers Of Local and Systemic Immunologic And Inflammatory A...mentioning
confidence: 99%